IPP and Changes in IPSS in Benign Prostatic Hyperplasia (BPH) Patients Treated with ?1-Blocker - Muhammad Ishak; Etriyel MYH; Peri Eriad Yunir (Indonesian Journal of Multidisciplinary Science, 2023)
Benign prostatic hyperplasia (BPH) is a benign enlargement of the prostate gland caused by the proliferation of epithelial cells and stroma, causing Lower Urinary Tract Symptoms (LUTS). One of the ways to treat BPH is through medical therapy with ?1-blockers. The success of medical therapy is influenced by many factors, one of which is Intravesical Prostatic Protrusion (IPP).  This study was a comparative prospective study that aimed to find the effect of IPP on response to therapy with ?1-blockers in BPH patients. IPSS was used as a measuring tool. IPP was examined using transabdominal ultrasound. The study was conducted from July 2020 to December 2020. Data were analyzed using the one way ANOVA average comparison test and Pearson correlation test. A sample of 30 patients was divided into 3 groups based on the IPP degree, namely grade I (<5mm), grade II (5-10mm) and grade III (> 10mm). There were no significant differences in the mean initial IPSS scores in each group, namely 19.6, 18.90, and 21.30 (p = 0.216). There was a significant decrease in mean IPSS after 1 month of ?1-blocker therapy. In addition, there was also found a significant correlation between the IPP value and the decrease in the final IPSS with a negative correlation. There is a significant correlation between the IPP degree and the decrease in IPSS in BPH patients after receiving ?1-blocker therapy as the higher the IPP degree, the lower the final IPSS improvement.